2019
DOI: 10.31235/osf.io/nmjf2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EFL Learners’ Perception about Integrating Blended Learning in ELT

Abstract: The study highlights English a Foreign Language (EFL) learners' perceptions about integrating Blended Learning (BL) to facilitate them completing their foundation year English courses at a Saudi university. The focus of the study was to investigate "the EFL learners' perception about integrating blended learning in their English Language Teaching (ELT) process". For this purpose, a survey was constructed in three subsections investigating the learners' viewpoints about BL as a platform: a) to improve learners'… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Similar findings were made by Aljaraideh & Al Bataineh (2019), who stated that blended learning increased students' digital skills, and Hussein Alsowayegh et al ( 2019), who reported that students were inspired to check additional social media accounts. Other researchers (Bukhari & Mahmoud Basaffar, 2019) who discovered that pupils were driven to learn indepen-dently concurred with this finding.…”
Section: Blended Learning In Esl Classrooms At Tertiary Institutionssupporting
confidence: 53%
“…Similar findings were made by Aljaraideh & Al Bataineh (2019), who stated that blended learning increased students' digital skills, and Hussein Alsowayegh et al ( 2019), who reported that students were inspired to check additional social media accounts. Other researchers (Bukhari & Mahmoud Basaffar, 2019) who discovered that pupils were driven to learn indepen-dently concurred with this finding.…”
Section: Blended Learning In Esl Classrooms At Tertiary Institutionssupporting
confidence: 53%
“…For example, Alsowayegh et al (2019) at King Abdulaziz University found that using online activities (i.e., watching videos related to the lesson and participating in discussion forums) in addition to in-person instruction improved university EFL learners' listening and speaking skills. Other studies surveying university EFL students' perceptions of employing the blended learning model in their English acquisition show positive attitudes towards this method (Al-Jarf, 2007;Alowedi, 2020;Bukhari & Basaffar, 2019;Gulnaz et al, 2019).…”
Section: E-learning Of English In Ksamentioning
confidence: 99%
“…In the Saudi context, the effectiveness of implementing a blended learning method to deliver English courses and students' perceptions of using this method of teaching has been investigated by many researchers at most Saudi universities (e.g., Al-Nofaie 2020; Alsowayegh, Bardesi, Garba and Sipra 2019;Bin Dahmash 2020;Bukhari and Basaffar 2019;Gulnaz, Althomali and Alzeer 2020). In her case study, Al-Nofaie (2020) compared the synchronous and asynchronous aspects of Blackboard.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The analysis of their experimental research revealed positive effects of using this method on students' engagement, satisfaction, teacher's role, the content and examination when learning English. In the same vein, Bukhari and Basaffar (2019) used a mixed method approach to investigate learners' viewpoints about blended learning. They also found positive attitudes towards this approach as it increased the learner's interest, interaction and autonomy.…”
Section: Review Of the Literaturementioning
confidence: 99%